POLITENESS STRATEGIES USED BY MAJOR CHARACTERS IN JANE AUSTEN’S NOVEL, PRIDE AND PREJUDICE - Syakur, Abd; Sudrajad, Wahyu; Masruroh, Masruroh (Universitas Islam Sumatera Utara (UISU), 2023)
The purpose of this study was to describe the language politeness employed by the major character in The Pride and Prejudice novel. The method used was descriptive qualitative. The researchers found: first, the data of positive politeness strategies and the data of negative politeness strategies were in line with Brown and Levinson's theory, 10 positive types of politeness strategies. The mostly used were: paying attention to the speaker’s interests, wants, requirements and commodities. When the speaker truly means “you” or “me”, he can employ the strategy of inclusiveness form to invoke the cooperative presumptions and rectify FTAs, giving or asking for explanations, insisting on reciprocity, goodness, sympathy, understanding, and cooperation. Out of 8 negative types of politeness strategies, the mostly used were: adopting a customarily indirect stance, not taking compliance for granted, expressing pessimism about one’s capacity or willingness, to reduce the burden, as cited from the FTAs as an illustration of a general principle. Then, three factors influenced the use of polite language, namely: social distance, power, and degree of impositions.